2022
DOI: 10.1186/s12905-022-01687-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of pelvic floor dysfunction and rehabilitation care amongst women in southeast China after radical hysterectomy: a qualitative study

Abstract: Objective To investigate the perceptions of pelvic floor dysfunction (PFD) and rehabilitation care amongst women after radical hysterectomy and to explore ways to improve quality of care. Methods Thirty-six women who underwent radical hysterectomy at a hospital in southeast China were enrolled via purposive sampling. Semi-structured in-depth interviews were conducted. The texts were analysed via qualitative content analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The OABSS has been developed to express all of the OAB symptoms in a single result, which is usually used in the objective diagnosis of OAB. 24 According to statistics from different countries, the prevalence of OAB among women ranges from 6.0% to 17.4%. 25 The prevalence of OAB in our studied population falls within this range.…”
Section: Discussionmentioning
confidence: 99%
“…The OABSS has been developed to express all of the OAB symptoms in a single result, which is usually used in the objective diagnosis of OAB. 24 According to statistics from different countries, the prevalence of OAB among women ranges from 6.0% to 17.4%. 25 The prevalence of OAB in our studied population falls within this range.…”
Section: Discussionmentioning
confidence: 99%
“…There may be short-term suffering like post-operation bleeding, fever, chest pain, infection, and long-term discomforts including the overactive pelvic floor, bladder pain, or urinary incontinence. Pelvic floor disorders are prevalent in China, and a meta-data analysis showed that around 31% of adult females suffered from urinary incontinence, which could lead to embarrassment and inconvenience in females' workplaces, exercises, social situations, etc [4]. One of the most severe symptoms is postpartum depression, also called "baby blues", which may be suffered by mothers from the first week after giving birth until up to 3 years time with symptoms of mood swings, anxiety, feelings of helplessness... A study made by Xinli Chi, and Peichao Zhang (et al) in 2016 examines 506 Chinese mothers within 3 years of delivery using an online survey [5].…”
Section: Physical and Mental Health Problems After Giving Birthmentioning
confidence: 99%